Thunderstorm response spectrum technique: Theory and applications. (1st February 2016) - Solari, Giovanni
Highlights: Thunderstorms are transient phenomena characterized by short duration. Structural response to transient phenomena is usually evaluated by the response spectrum technique. This paper extends the response spectrum technique from earthquakes to thunderstorms. The equivalent static force is the product of the peak wind loading by the equivalent response spectrum. Abstract: This paper is part of a research project that started from the consideration that thunderstorms are transient phenomena with short duration and the structural response to transient phenomena, most notably to earthquakes, is traditionally evaluated by the response spectrum technique. Based on this consideration, a "new" method is formulated that generalizes the "old" response spectrum technique from earthquakes to thunderstorms. A previous paper addressed this problem for ideal point-like Single-Degree-Of-Freedom systems subjected to wind actions perfectly coherent over the exposed structural surface. The present paper generalizes this formulation to real space Multi-Degree-Of-Freedom systems subjected to partially coherent wind fields with assigned velocity profile and turbulence properties; for sake of simplicity, in this stage of the research, the structure is modeled as a continuous slender vertical cantilever beam. Analyses are carried out by making recourse to the equivalent wind spectrum technique, a method developed for synoptic stationary winds, the use of which is extended here to non-synoptic non-stationary conditions. In spite of a rather complex formulation, the application of the thunderstorm response spectrum technique is straightforward: the equivalent static force is the product of the peak wind loading by a non-dimensional quantity, the equivalent response spectrum, given by a simple diagram. Its derivation represents one of the most typical features of this method: it is based on the joint numerical processing of a set of measured thunderstorm records and an analytical model that conceptually reconstructs the complete wind field around the measured data. In virtue of its characteristics, the thunderstorm response spectrum technique is particularly suitable for rapid engineering calculations and simple code applications.